Electrode for secondary battery
By employing a multilayer structure and different molecular weight carboxymethyl cellulose and styrene-butadiene rubber adhesives in the secondary battery electrode design, the balance between electrode adhesion and resistance was solved, thereby improving battery performance.
Patent Information
- Application Number
- CN202110796091.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-15
- Filing Date
- 2021-07-14
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2041-07-14
AI Technical Summary
The electrodes of existing secondary batteries are difficult to balance between high adhesion strength and low resistance, which leads to deterioration of electrode performance and increased manufacturing costs. In particular, the adhesion is easily damaged when using active materials with high expansion and contraction rates, and the active material layer is pushed and squeezed during the rolling process, affecting battery capacity and efficiency.
A multi-layer electrode design is adopted, in which the first electrode mixture layer uses low molecular weight carboxymethyl cellulose and styrene-butadiene rubber as binders, and the second electrode mixture layer uses high molecular weight carboxymethyl cellulose and styrene-butadiene rubber. By adjusting the molecular weight and composition of the binders, the adhesion between the current collector and the active material and the cohesion between the active materials are improved, while the internal resistance of the electrode is reduced.
This improves the adhesion between the electrode current collector and the active material, as well as the cohesive force among the active materials, and reduces the resistance within the electrode, thereby enhancing the capacity and lifespan characteristics of the secondary battery.
Smart Images

Figure CN113948670B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0087785, filed with the Korean Intellectual Property Office on July 15, 2020. The entire disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to an electrode for a secondary battery, and more specifically, to an electrode for a secondary battery having improved adhesive strength. Background Technology
[0004] With technological advancements and increasing demand for mobile devices, the need for secondary batteries as an energy source is rapidly growing, and among these secondary batteries, lithium-ion batteries with high energy density and voltage are commercially available. These secondary batteries have a structure in which electrode assemblies capable of being charged and discharged, having both a positive / separator / negative electrode structure, are mounted on a battery casing. In this case, the positive and negative electrodes are manufactured by applying electrode active materials, etc., to one or both surfaces of a metal current collector, followed by drying and rolling.
[0005] Currently, electrode plates with high bonding strength can be manufactured using polyvinylidene fluoride (PVdF), which is widely used as a binder for both positive and negative electrodes. However, PVdF covers the active material in the same full state as polymer fibers, thus degrading the inherent battery performance of the electrode active material in terms of capacity and efficiency. Furthermore, in the case of PVdF, which lacks flexibility, the bonding is easily disrupted when materials with large specific surface areas and high expansion and contraction rates during charging and discharging (such as natural graphite or metal-based active materials) are used as electrode active materials, and cycle characteristics are easily degraded.
[0006] Furthermore, as the active material loading per unit area of the electrode increases, the active material layer is pushed out during rolling, and the loading per unit area falls below the initial expected value. Therefore, there is a problem that the total electrode thickness further increases to achieve the desired capacity, thus increasing manufacturing costs. Therefore, there is a strong need to develop a negative electrode that can improve the performance of secondary batteries and reduce the resistance within the electrode due to increased adhesion between the negative electrode current collector and the active material, as well as increased cohesion between active materials. Summary of the Invention
[0007] This summary is provided to present in a simplified form some of the choices of concepts that will be further described in the detailed description below. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to help determine the scope of the claimed subject matter.
[0008] One aspect of the present invention is to provide an electrode for a secondary battery that can reduce the electrical resistance of the secondary battery while ensuring the adhesive force between the electrode current collector and the active material and the cohesive force between the active materials, and to provide a secondary battery including the electrode.
[0009] According to one aspect of the present invention, an electrode for a secondary battery includes a current collector, a first electrode mixture layer disposed on at least one surface of the current collector and comprising carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), and a second electrode mixture layer disposed on the first electrode mixture layer and comprising carboxymethyl cellulose. The weight-average molecular weight of the carboxymethyl cellulose contained in the first electrode mixture layer is less than that of the carboxymethyl cellulose contained in the second electrode mixture layer.
[0010] The weight-average molecular weight of carboxymethyl cellulose contained in the first electrode mixture layer can be 40 × 10⁻⁶. 4 Up to 300×10 4 .
[0011] The weight-average molecular weight of carboxymethyl cellulose contained in the second electrode mixture layer can be 350 × 10⁻⁶. 4 Up to 600×10 4 .
[0012] Based on the total monomer content, the styrene-butadiene rubber contained in the first electrode mixture layer may contain 40 to 90 mol% butadiene monomer. The second electrode mixture layer may further contain styrene-butadiene rubber.
[0013] The weight of styrene-butadiene rubber contained in the second electrode mixture layer may be equal to or less than the weight of styrene-butadiene rubber contained in the first electrode mixture layer.
[0014] Based on the total monomer content, the styrene-butadiene rubber contained in the second electrode mixture layer may contain 5 to 35 mol% butadiene monomer.
[0015] Based on the total weight of the first electrode mixture layer, the first electrode mixture layer may contain 0.6 to 2.0 wt% carboxymethyl cellulose and 2.0 to 5.0 wt% styrene-butadiene rubber.
[0016] Based on the total weight of the second electrode mixture layer, the second electrode mixture layer may contain 0.6 to 2.0% by weight of carboxymethyl cellulose and less than 2.0% by weight of styrene-butadiene rubber.
[0017] The thickness of the first electrode mixture layer can be 10 to 40 μm.
[0018] The thickness of the second electrode mixture layer can be from 10 to 100 μm.
[0019] This electrode can be the negative electrode. Attached Figure Description
[0020] The above and other aspects, features, and advantages of the present invention will become more clearly understood from the following detailed description, taken in conjunction with the accompanying drawings, wherein:
[0021] Figure 1 An electrode according to an exemplary embodiment of the present invention is illustrated schematically. Detailed Implementation
[0022] The following detailed description is provided to assist the reader in gaining a comprehensive understanding of the methods, apparatus, and / or systems described herein. However, various variations, modifications, and equivalents of the methods, apparatus, and / or systems described herein will be apparent to those skilled in the art. The order of operations described herein is merely illustrative and is not limited to those set forth herein, but can be altered as will be apparent to those skilled in the art, except for operations that must occur in a specific order. Furthermore, for clarity and brevity, descriptions of functions and constructions well-known to those skilled in the art may be omitted.
[0023] The features described herein may be embodied in different forms and are not to be construed as limited to the examples described herein. Rather, the examples described herein have been provided so that the invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.
[0024] In this document, it should be noted that the use of the term "may" in relation to implementation schemes or examples, for example, regarding what an implementation scheme or example may include or implement, means that there is at least one implementation scheme or example that includes or implements the feature, while all examples and instances are not limited thereto.
[0025] Throughout the specification, when an element, such as a layer, region, or substrate, is described as "on another element," "connected to," or "coupled to" another element, it can be directly "on another element," "connected to," or "coupled to" another element, or there can be one or more other elements in between. Conversely, when an element is described as "directly on another element," "directly connected to," or "directly coupled to" another element, there cannot be any other elements intervening between them.
[0026] As used herein, the term “and / or” includes any one and any combination of any two or more associated listed items.
[0027] Although terms such as “first,” “second,” and “third” may be used herein to describe various components, assemblies, regions, layers, or parts, these components, assemblies, regions, layers, or parts are not limited by these terms. Rather, these terms are used only to distinguish one component, assembly, region, layer, or part from another. Thus, without departing from the teachings of the examples, the first component, assembly, region, layer, or part mentioned in the examples described herein may also be referred to as the second component, assembly, region, layer, or part.
[0028] For ease of description, this document uses spatially relative terms such as “above,” “upper,” “below,” and “lower” to describe the relationship between one element and another as shown in the figures. These spatially relative terms are intended to encompass different orientations of the device in use or operation, in addition to those described in the figures. For example, if the device in the figures is flipped, an element described as “above” or “upper” relative to another element would be “below” or “lower” relative to the other element. Thus, depending on the spatial orientation of the device, the term “above” includes both above and below orientations. The device may also be oriented in other ways (e.g., rotated 90 degrees or in other directions), and the spatially relative terms used herein will be interpreted accordingly.
[0029] The terminology used herein is for the purpose of describing various examples only and is not intended to limit this disclosure. The articles “a,” “an,” and “the” are also intended to include plural forms unless the context clearly indicates otherwise. The terms “comprise,” “include,” and “have” specify the presence of the stated feature, number, operation, component, element, and / or combination thereof, but do not preclude the presence or addition of one or more other features, numbers, operations, components, elements, and / or combinations thereof.
[0030] Due to manufacturing techniques and / or tolerances, the shapes illustrated in the figures may vary. Therefore, the examples described herein are not limited to the specific shapes illustrated in the figures, but include shape variations that occur during manufacturing.
[0031] Having understood the inventive scope of this application, it will be apparent that the features of the examples described herein can be combined in various ways. Furthermore, although the examples described herein have multiple configurations, other configurations are also possible after understanding the inventive scope of this application.
[0032] The accompanying drawings may not be drawn to scale, and for clarity, illustration, and convenience, the relative dimensions, scale, and depiction of elements in the drawings may be enlarged.
[0033] In the following description, exemplary embodiments of the invention will be illustrated with reference to various examples. However, embodiments of the invention can be modified in various other ways, and the scope of the invention is not limited to the embodiments described below.
[0034] According to an exemplary embodiment, an electrode for a secondary battery is provided, and more specifically, an electrode for a secondary battery with improved adhesive strength is provided.
[0035] The binder used in electrode manufacturing needs to possess adhesive properties, where both the adhesive force between the current collector and the active material and the cohesive force between the active materials can be provided simultaneously. If the adhesive force is not guaranteed, the binder can be a factor affecting the capacity reduction and stability of the secondary battery. To ensure this adhesive performance, increasing the binder content or using a binder with relatively strong adhesive force can be considered. However, in this case, an increase in the secondary battery resistance is unavoidable.
[0036] Therefore, the inventors have achieved this invention by using adhesives with different properties in the upper and lower layers to manufacture electrodes with a multilayer structure, thereby ensuring the adhesion between the electrode current collector and the active material as well as the cohesive force between the active materials, while reducing the resistance within the electrode.
[0037] According to an exemplary embodiment of the present invention, an electrode for a secondary battery includes a current collector 10; a first electrode mixture layer 20 disposed on at least one surface of the current collector 10 and comprising carboxymethyl cellulose and styrene-butadiene rubber; and a second electrode mixture layer 30 disposed on the first electrode mixture layer 20 and comprising carboxymethyl cellulose, wherein the weight-average molecular weight of the carboxymethyl cellulose contained in the first electrode mixture layer 20 is lower than the weight-average molecular weight of the carboxymethyl cellulose contained in the second electrode mixture layer 30.
[0038] In an exemplary embodiment of the present invention, carboxymethyl cellulose is used as a first adhesive and styrene-butadiene rubber is used as a second adhesive to ensure the adhesion between the electrode current collector and the active material, as well as the cohesion between the active material layers.
[0039] Depending on their weight-average molecular weight, the first binder, carboxymethyl cellulose, possesses different properties. According to an exemplary embodiment of the present invention, preferably, the weight-average molecular weight of the carboxymethyl cellulose contained in the first electrode mixture layer can be lower than that of the carboxymethyl cellulose contained in the second electrode mixture layer.
[0040] Specifically, high molecular weight carboxymethyl cellulose can improve the adhesion between the electrode current collector and the active material, but it has relatively high resistance and relatively low dispersibility. Low molecular weight carboxymethyl cellulose, on the other hand, has slightly lower adhesion strength than high molecular weight carboxymethyl cellulose, but it has relatively low resistance and excellent dispersibility. Therefore, by making the weight-average molecular weight of the carboxymethyl cellulose contained in the first electrode mixture layer 20 lower than that contained in the second electrode mixture layer 30, the adhesion between the electrode current collector and the active material can be improved, and the resistance can also be reduced.
[0041] The weight-average molecular weight of carboxymethyl cellulose contained in the first electrode mixture layer 20 can be 40 × 10⁻⁶. 4 Up to 300×10 4 , specifically, 60×10 4 Up to 200×10 4 If the weight-average molecular weight of carboxymethyl cellulose contained in the first electrode mixture layer 20 is less than 40 × 10⁻⁶. 4 If the viscosity of the slurry is too low, the coating process may be difficult, especially if it exceeds 300×10. 4 If the resistance is relatively high and the material contains undissolved substances, it may be difficult to achieve the effect of this invention in improving the cohesive force between active materials and reducing the resistance within the electrode.
[0042] The weight-average molecular weight of carboxymethyl cellulose contained in the second electrode mixture layer 30 can be 350 × 10⁻⁶. 4 Up to 600×10 4 , specifically, 350×10 4 Up to 450×10 4 If the weight-average molecular weight of carboxymethyl cellulose contained in the second electrode mixture layer 30 is less than 350 × 10⁻⁶. 4 If the cohesion between the active material layers is low, partial detachment of the active material layers may occur during the notch process, and the battery's lifespan characteristics may also deteriorate. If it exceeds 600 × 10⁻⁶... 4 Due to the undissolved products of carboxymethyl cellulose, the resistance may increase significantly, which may degrade the battery characteristics.
[0043] On the other hand, the first electrode mixture layer 20 may contain styrene-butadiene rubber (SBR) as a second adhesive, and the second electrode mixture layer 30 may also contain SBR as a second adhesive if desired. In this case, it is preferable that the properties of the SBR included in the first electrode mixture layer and the second electrode mixture layer may be different from each other. According to one embodiment, the amount of SBR included in the second electrode mixture layer may be equal to or less than the amount of SBR included in the first electrode mixture layer.
[0044] In this invention, the styrene-butadiene rubber used as the second adhesive refers to a polymer comprising repeating units of styrene-derived structures and repeating units of butadiene-derived structures. In the styrene-butadiene rubber, the repeating units of the butadiene-derived structures can be, for example, repeating units derived from structures derived from 1,3-butadiene or derivatives thereof, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, or 2-ethyl-1,3-butadiene, etc. Furthermore, the repeating units of the styrene-derived structures can be repeating units derived from structures of styrene, where styrene is an aromatic vinyl compound, such as styrene, α-methylstyrene, p-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene, 1-vinyl-5-hexylnaphthalene, etc., or structures of their derivatives.
[0045] Typically, in styrene-butadiene rubber (SBR), styrene and butadiene retain mechanical strength and exhibit adhesive properties. The SBR used in the secondary battery according to embodiments of the present invention can preferably be synthesized by adding monomers in addition to styrene and butadiene that impart electrolyte-friendly properties to improve battery characteristics. There are no particular limitations on the monomers used; for example, acrylate-based monomers, acrylonitrile-based monomers, etc., can be used.
[0046] On the other hand, in embodiments of the present invention, based on the total monomer content, the styrene-butadiene rubber of the first electrode mixture layer 20 may contain 40 to 90 mol% butadiene monomer, more specifically, 50 to 85 mol% butadiene monomer. If the butadiene monomer content is less than 40 mol%, the interlayer adhesion between the current collector and the active material may be relatively low, and therefore, the outermost punched surface may peel off upon immersion in the electrolyte. If its content exceeds 90 mol%, the resistance is high, and the affinity with the electrolyte is low, leading to an increase in battery resistance.
[0047] On the other hand, based on the total content of monomers, the styrene-butadiene rubber of the second electrode mixture layer 30 can contain 5 to 35 mol% butadiene monomers, specifically 5 to 30 mol%. If the butadiene monomer content is less than 5 mol%, the mechanical strength of the styrene-butadiene rubber decreases, thus the adhesion may decrease, and the battery life characteristics may deteriorate. If its content exceeds 35 mol%, the effect of reducing the internal resistance of the electrode according to the present invention may be difficult to achieve due to the low affinity with the electrolyte.
[0048] In this way, by using styrene-butadiene rubber with a relatively high content of styrene-butadiene monomer as a second adhesive in the first electrode mixture layer 20 that contacts the electrode current collector 10, the adhesion to the electrode current collector can be improved. By using styrene-butadiene rubber with a low content of styrene-butadiene monomer in the second electrode mixture layer 30, the resistance can be significantly reduced overall.
[0049] On the other hand, carboxymethyl cellulose may be included in the first electrode mixture layer 20 in an amount of 0.6 to 2.0% by weight, specifically 0.8 to 1.8% by weight, based on the total weight of the first electrode mixture layer 20. If the content of carboxymethyl cellulose included in the first electrode mixture layer 20 is less than 0.6% by weight, it may be difficult to disperse the active material, resulting in low viscosity and potentially poor processability during the coating process. If the content exceeds 2.0% by weight, the viscosity is too high, and the flowability is low, thus potentially worsening processability and potentially degrading battery characteristics.
[0050] Furthermore, the first electrode mixture layer 20 may contain styrene-butadiene rubber (SBR) in an amount of 2.0 to 5.0% by weight, specifically 2.0 to 3.5% by weight, based on the total weight of the first electrode mixture layer 20. If the content of SBR in the first electrode mixture layer 20 is less than 2.0% by weight, detachment may occur during cutting due to low adhesive strength, and if the content exceeds 5.0% by weight, the resistance may increase and the battery characteristics may deteriorate.
[0051] In the second electrode mixture layer 30, carboxymethyl cellulose may be included in an amount of 0.6 to 2.0% by weight, specifically 0.8 to 1.8% by weight, based on the total weight of the second electrode mixture layer 30. If the content of carboxymethyl cellulose included in the second electrode mixture layer 30 is less than 0.6% by weight, it may be difficult to ensure the cohesive force between the active material layers, and scrap and partial detachment may occur during the cutting process. If the content exceeds 2.0% by weight, it may be difficult to obtain the effects of the present invention for improving the cohesive force between active materials and reducing the resistance within the electrode due to high resistance.
[0052] Additionally, the second electrode mixture layer 30 may contain styrene-butadiene rubber in an amount of less than 2.0% by weight, specifically less than 1.5% by weight, based on the total weight of the second electrode mixture layer 30. If the content of styrene-butadiene rubber in the second electrode mixture layer 30 exceeds 2.0% by weight, the resistance increases, and the battery characteristics may deteriorate.
[0053] On the other hand, the thickness of the first electrode mixture layer 20 is preferably from 10 μm to 40 μm. If the thickness is less than 10 μm, scratching of the active material or tearing of the current collector may occur during the coating process. If the thickness exceeds 40 μm, the effectiveness of the present invention may be reduced due to the use of excessive SBR with a high styrene-butadiene content. Additionally, the thickness of the second electrode mixture layer 30 is preferably from 10 μm to 120 μm. If the thickness is less than 10 μm, the coating process may be difficult because the thickness is similar to the primary particle size of the electrode active material. On the other hand, if the thickness exceeds 120 μm, the concentration gradient of styrene-butadiene rubber between the first and second electrode mixture layers is relatively large, and the effectiveness of the present invention may not be achieved. Therefore, in an exemplary embodiment of the present invention, the thickness ratio of the first electrode mixture layer to the second electrode mixture layer may be from 1:1 to 1:3. Furthermore, the mixture density of the first and second electrode mixture layers having the above-mentioned thicknesses may be 1.65 g / cc.
[0054] The method for manufacturing an electrode of a secondary battery for use in the exemplary embodiments according to the present invention is not particularly limited, and may be performed by a known method. For example, a first slurry containing an electrode active material, a binder and a conductive material in a solvent is applied onto an electrode current collector by a method such as bar coating, casting, spraying and the like, and dried to form a first electrode mixture layer; thereafter, a second slurry containing an electrode active material, a binder and a conductive material in a solvent is applied onto the first electrode mixture layer by a method such as bar coating, casting, spraying and the like, and dried, thereby manufacturing the electrode for a secondary battery.
[0055] For example, dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water may be used as the solvent. As for the amount of the solvent used, in consideration of the coating thickness of the composition for forming the electrode active material layer and the manufacturing yield, the amount of the solvent only needs to be sufficient to dissolve and disperse the electrode active material, the conductive material and the binder, and may provide a viscosity capable of exhibiting excellent thickness uniformity when subsequently applied to form the first electrode active material layer.
[0056] On the other hand, the electrode may be a negative electrode, and the secondary battery including the negative electrode according to the present invention has reduced electrode resistance, and thus the capacity characteristics and life characteristics of the battery may be significantly improved.
[0057] At least one carbon-based material selected from, for example, crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low-crystalline soft carbon, carbon black, acetylene black, Ketjen black, Super P, graphene and carbon fiber, a silicon-based material, a metal composite oxide such as Li x Fe₂O₃ (0≤x≤1), Li x WO₂ (0≤x≤1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Group 1, Group 2 and Group 3 of the Periodic Table of Elements, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8) and the like, lithium metal, lithium alloy, silicon alloy, tin alloy, metal oxides such as SiO, SiO₂, SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ and Bi₂O₅, conductive polymers such as polyacetylene and the like, Li-Co-Ni-based materials, titanium oxide and the like may be used as the negative electrode active material.
[0058] Conductive materials are used to impart conductivity to electrodes, and there are no particular limitations as long as they are conductive and do not cause side reactions with other components of the secondary battery. Specific examples of conductive materials may include graphite, such as natural graphite, artificial graphite, etc.; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lampblack, thermal cracking black, carbon fiber, etc.; metal powder particles or metal fibers, such as copper, nickel, aluminum, silver, etc.; conductive whiskers, such as zinc oxide and potassium titanate, etc.; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polystyrene derivatives, etc., and one or a mixture of two or more of them may be used alone.
[0059] Example
[0060] The invention will be described in more detail below with reference to embodiments. These embodiments are provided to explain the invention in more detail, but the invention is not limited thereto.
[0061] 1. Preparation of the negative electrode
[0062] A first negative electrode slurry using artificial graphite as the negative electrode active material was coated onto copper foil and dried to form a first negative electrode mixture layer. A second negative electrode slurry was then coated onto the first negative electrode mixture layer and dried to prepare the negative electrode. Carboxymethyl cellulose was used as the first binder, and styrene-butadiene rubber was used as the second binder. The average weight ratio of the first binder to the second binder in the first electrode mixture layer and the second electrode mixture layer was 1.2:1.5. The content and molecular weight of carboxymethyl cellulose and styrene-butadiene rubber contained in the first and second negative electrode mixture layers were controlled, as shown in Table 1.
[0063] The molecular weight of carboxymethyl cellulose shown in Table 1 is 0.05% by weight, which is the value obtained by gel permeation chromatography (GPC) analysis after the dissolution and filtration process.
[0064] 2. Manufacturing of lithium secondary batteries
[0065] A positive electrode is manufactured by coating an aluminum foil with a slurry containing LiCoO2 as the positive electrode active material and then drying it. After inserting a polyolefin separator between the prepared positive and negative electrodes, an electrolyte containing 1M LiPF6 is injected into a solvent in which ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a volume ratio of 30:70, thereby manufacturing a coin-shaped lithium secondary battery.
[0066] 3. Adhesive force measurement experiment
[0067] (1) Measure the adhesion between the negative electrode current collector and the negative electrode mixture layer.
[0068] After cutting the prepared negative electrode into 18mm wide and 150mm long pieces, an 18mm wide tape was attached to the negative electrode current collector, and a roller with a 2kg load was used to ensure full adhesion of the tape to the current collector. Subsequently, double-sided tape was used to adhere the negative electrode mixture layer to one side of a tensile testing machine (DS2-50N, IMADA), and the tape attached to the negative electrode current collector was then fixed to the opposite side of the tensile testing machine to measure the adhesive force. The results are shown in Table 1.
[0069] (2) Measurement of cohesive force between negative electrode mixture layers
[0070] The surface of the prepared negative electrode mixture layer was cut by more than 10 μm using sandpaper with a grit of 1000 grit or higher, and then cut into dimensions of 18 mm wide and 150 mm long. Next, adhesive tape with a width of 18 mm was attached to the negative electrode mixture layer and fully bonded using a roller with a 2 kg load. Subsequently, double-sided adhesive tape was used to adhere the negative electrode mixture layer to one side of a tensile tester, and then the tape attached to the negative electrode current collector was fixed to the opposite side of the tensile tester to measure its adhesive force. The results are shown in Table 1.
[0071] (3) Measurement of cyclic capacity retention
[0072] After the manufactured coin-shaped lithium secondary batteries were left to stand for 10 hours, they were charged and discharged once at a rate of 0.1C to carry out the chemical conversion process. Subsequently, two more charge-discharge cycles at 0.1C were performed to measure the cycle capacity of the manufactured batteries and to identify any defects. Cycle capacity retention was measured by repeating charge-discharge cycles at 0.3C. The results are shown in Table 1.
[0073] [Table 1]
[0074]
[0075] In Example 1, it was confirmed that, compared to the comparative example, by applying CMC carboxymethyl cellulose with a molecular weight of 4.2 million to the upper layer and CMC carboxymethyl cellulose with a molecular weight of 3 million to the lower layer, not only was the adhesion of the electrode significantly improved, but the capacity retention was also significantly improved. This demonstrates that the molecular weight of CMC has a significant impact on the adhesion of the electrode.
[0076] As can be seen from Examples 2 and 3, where the butadiene content of the upper SBR is 20 mol%, it can be determined that the cycle capacity retention increases as the mol% of butadiene in the SBR of the second negative electrode mixture layer decreases. Specifically, it can be seen that, in terms of adhesion and lifetime characteristics, Example 2 is also superior to Example 3, which uses 40 mol% butadiene in the lower SBR, in terms of butadiene content.
[0077] Referring to Example 4, it can be seen that the use of CMC with a molecular weight of 1.4 million and SBR with a butadiene content of 80 mol% in the lower layer improves the electrode adhesion, while the use of CMC with a molecular weight of 4.2 million and SBR with a butadiene content of 20 mol% in the upper layer improves the resistance and lifetime characteristics.
[0078] Example 5 was provided by controlling the CMC / SBR content of the upper and lower layers, and it was determined that, compared with Example 4, the adhesion was further improved with the increase of the SBR content in the lower layer, and the lifetime characteristics were improved because SBR, which may act as a resistor, was not added to the upper layer.
[0079] In Comparative Example 1, the molecular weight of the CMC contained in the second electrode mixture layer (upper layer) is less than 3.5 million (this is within the scope defined by the present invention). In Comparative Example 2, the molecular weight of the CMC contained in the first electrode mixture layer (lower layer) is 3.5 million, which is more than 3 million (this is within the scope defined by the present invention). It can be confirmed that the comparative examples are not ideal in terms of cycle capacity retention due to the increase in resistance.
[0080] In Comparative Example 3, when an ultra-low molecular weight CMC of 350,000 was applied to the lower layer, it was observed that not only was the electrode adhesion significantly reduced, but the battery capacity retention was also significantly decreased. Due to the low thickening effect of CMC with a molecular weight less than 400,000, it is primarily used for dispersions and is not suitable for the production of negative electrode slurries. Furthermore, it can be seen that by covering the active material, the repulsion effect is significantly reduced, leading to decreased phase stability of the slurry and problems such as SBR aggregation.
[0081] As in Comparative Example 4, when CMC with a weight-average molecular weight of over 4 million is used in the lower layer, it can be seen that the capacity retention rate decreases slightly due to the increase in resistance.
[0082] As described above, according to the exemplary embodiments, the adhesion between the electrode current collector and the active material, as well as the cohesive force between the active materials, can be improved, and the resistance within the electrode can be reduced. As a result, the capacity and lifespan characteristics of the battery can be significantly improved.
[0083] While this invention includes specific examples, it will be apparent to those skilled in the art that various changes in form and detail may be made in these examples without departing from the spirit and scope of the claims and their equivalents. The examples described herein are to be considered descriptive only and not for limiting purposes. The description of features or aspects in each embodiment is to be considered applicable to similar features or aspects in other embodiments. Suitable results may be obtained if the described techniques are performed in a different order, and / or if components in the described system, architecture, device, or circuit are combined in a different manner, and / or replaced or supplemented by other components or their equivalents. Therefore, the scope of this invention is not limited by the detailed description but by the claims and their equivalents, and all variations within the scope of the claims and their equivalents should be construed as included in this invention.
Claims
1. An electrode for a secondary battery, comprising: current collector; A first electrode mixture layer comprising carboxymethyl cellulose and styrene-butadiene rubber is disposed on at least one surface of the current collector; as well as A second electrode mixture layer comprising carboxymethyl cellulose is disposed on the first electrode mixture layer. The weight-average molecular weight of the carboxymethyl cellulose contained in the first electrode mixture layer is less than that of the carboxymethyl cellulose contained in the second electrode mixture layer. Based on the total monomer content, the styrene-butadiene rubber contained in the first electrode mixture layer contains 40 to 90 mol% butadiene monomer, and the carboxymethyl cellulose contained in the first electrode mixture layer has a weight-average molecular weight of 40 × 10⁻⁶. 4 Up to 300×10 4 , The second electrode mixture layer does not contain styrene-butadiene rubber.
2. An electrode for a secondary battery, comprising: current collector; A first electrode mixture layer comprising carboxymethyl cellulose and styrene-butadiene rubber is disposed on at least one surface of the current collector; as well as A second electrode mixture layer comprising carboxymethyl cellulose is disposed on the first electrode mixture layer. The weight-average molecular weight of the carboxymethyl cellulose contained in the first electrode mixture layer is less than that of the carboxymethyl cellulose contained in the second electrode mixture layer. Based on the total monomer content, the styrene-butadiene rubber contained in the first electrode mixture layer contains 40 to 90 mol% butadiene monomer, and the carboxymethyl cellulose contained in the first electrode mixture layer has a weight-average molecular weight of 40 × 10⁻⁶. 4 Up to 300×10 4 , The second electrode mixture layer comprises styrene-butadiene rubber, which, based on the total monomer content, comprises 5 to 35 mol% butadiene monomer.
3. The electrode for a secondary battery according to claim 1 or 2, wherein the carboxymethyl cellulose contained in the second electrode mixture layer has a weight-average molecular weight of 350 × 10⁻⁶. 4 Up to 600×10 4 .
4. The electrode for a secondary battery according to claim 2, wherein the weight of the styrene-butadiene rubber contained in the second electrode mixture layer is equal to or less than the weight of the styrene-butadiene rubber contained in the first electrode mixture layer.
5. The electrode for a secondary battery according to claim 1 or 2, wherein the first electrode mixture layer comprises 0.6 to 2.0 wt% carboxymethyl cellulose and 2.0 to 5.0 wt% styrene-butadiene rubber based on the total weight of the first electrode mixture layer.
6. The electrode for a secondary battery according to claim 1 or 2, wherein, based on the total weight of the second electrode mixture layer, the second electrode mixture layer comprises 0.6 to 2.0 wt% carboxymethyl cellulose and less than 2.0 wt% styrene-butadiene rubber.
7. The electrode for a secondary battery according to claim 1 or 2, wherein the thickness of the first electrode mixture layer is 10 µm to 40 µm.
8. The electrode for a secondary battery according to claim 1 or 2, wherein the thickness of the second electrode mixture layer is from 10 µm to 100 µm.
9. The electrode for a secondary battery according to claim 1 or 2, wherein the electrode is a negative electrode.
Citation Information
Patent Citations
Improved apparatus and method for measuring condensation and / or corrosion progression
KR1020200087785A
Anode for secondary battery, manufacturing method therefor, and secondary battery comprising same
CN107925058A
Lithium secondary battery manufacturing method
JP2013089422A
Negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
WO2020110690A1
